ADHERENCE TO TREATMENT AMONG HYPERTENSIVE PATIENTS AS A RESULT OF SPECIALISED PHARMACEUTICAL CARE - Mariya Ivanova; Anna Todorova; Lora Georgieva; Magdalena Pesheva (Peytchinski Publishing, 2022)
Arterial hypertension (AH) is one of the main risk factors for cardiovascular diseases and mortality among the population. Major problems in treating hypertension are the lack of adherence and poor blood pressure control. Purpose: To study the level of adherence to pharmacotherapy among hypertensive patients after the provision of specialised pharmaceutical care. Materials/Methods: Pharmaceutical care has been provided through a custom-made algorithm for consulting hypertensive patients, designed by the authors. Community pharmacists, involved in the study, have been trained in advance to provide specialised pharmaceutical care to hypertensive patients. A direct anonymous questionnaire has been delivered to hypertensive patients. The questionnaire consists of two parts. The first part includes questions about demographic details, lifestyles, the frequency of blood pressure measurement, etc., and the second part is a validated tool - the Morisky Medication Adherence Scale. Results: The study involved 50 patients with AH: 53% women and 47% men. After pharmaceutical care was provided through the established algorithm, 84% of the surveyed patients reported having no difficulties in the use of the prescribed medicines, and only 16% reported difficulties. Good management of blood pressure was observed in 73% of the respondents, while poor control was reported in only 27%. The Morisky coefficient for the study group was3.74, at a maximum score of 4, where the score for men was3.75 and for women - 3.72. Conclusions: The studied sample group shows a very high level of adherence to the treatment and hence good blood pressure control. It can be assumed that the achieved outcomes are due to the specialised pharmaceutical care performed in accordance with the established algorithm.